Anmeldelser - Erler, Annette (Danish Yearbook of Musicology, 2001)
Review of: Hans Weisethaunet: The Performance of Everyday Life. The Gaine of Nepal (Acta Humaniora 44). Universitetsforlaget/Scandinavian University Press, Oslo 1998 The Nepalese Blues, The Real Folk Music of Nepal. Performances and Narratives of the Wandering Gaine Musicians (Compiled by Hans Weisethaunet). Travelling Records, Oslo 1997. TR-001-2